Hellenistic influence and twins in the Gospel of Mark: fiery angels - Pettis, Jeffrey B. (Lexington Books, 2024)
"This book explores the influence of Hellenistic culture in the Gospel of Mark with a focus on Jesus' twin disciples James and John. Jesus gives them the name Boanerges, "Sons of Zeus," referring to the Dioscuri, mythological figures known for their saving action in times of danger and distress"--